Human papillomavirus as an important factor in the development of oropharyngeal cancer - modern diagnostics and new therapeutic methods - Madoń, Joanna; Czechowicz, Marta; Gadziński, Patryk (Quality in Sport, 2025)
Background. The article focuses on epidemiological trends observed globally over the pastfew decades, which demonstrate a dynamic increase in the incidence of HPV-positive OPC. A significant part of the paper is a discussion of the latest therapeutic and diagnostic methods, enabling the dynamic development of clinical management. Aim. The aim of this article was to present the current state of knowledge regarding the impact of HPV infection on the development of OPC. Material and methods. The review methodology included an analysis of 28 publications retrieved from the PubMed database, selected based on their currency and relevance to the research topic. The article primarily includes work published between 2018 and 2024, with the largest possible number of participants included. Results. HPV-associated OPC is currently one of the fastest-growing types of head and neck cancer worldwide. HPV types 16 and 18 are responsible for the majority of cases. The disease typically has a better prognosis than its HPV-negative counterparts, which is due to the different tumor biology. The introduction and widespread use of HPV vaccinations is a key element of global prevention, potentially significantly reducing the number of new cases in the future. Conclusions. Despite the dynamically developing knowledge about the HPV virus, we still need new diagnostic and therapeutic techniques to more effectively treat patients with OPC.